Preparation and Colloid Chemical Properties of New Surfactant Derivatives of Chitosan - Chernukhina, A. I.; Lazareva, E. V.; Gabrielyan, G. A.; Gal’braikh, L. S. (Fibre chemistry, 2016)
This paper presents the investigation of interaction of chitosan with carboxylate surfactants – cetyl oligo ethylene succinate and 1-stearoyl-2-hydroxypropyl-3-succinate. It is shown that depending on the type of surfactant and the ratio of components, viscous solutions or colloidal dispersions form on interaction with chitosan. For solutions of chitosan – surfactant derivatives a significant non-additive decrease in surface tension is characteristic, making them useful for obtaining stable emulsions of oil in water.